(3OhQ GdbVGA ai GdeSGAdI GdJCOjHjI ddehXa GdYGe (B: s (3OQGSI JMdjdjI ebGQfI (B/ s - (3eMeO QGei MSjf YHOGdbGOQs; (3LGHQ LGO fUGQ s; (3jSQi eMeO GdYUGQ s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2015)
(3JfGhdJ GdQSGdI OQGSI GdfXGe GdbVGFi ai GdJCOjH(B: (3HjGf eGgjI GdSdWI GdJCOjHjI h CfXeJgG h JWHjbGJ gPg GdCfXeI ai GdbGfhf GdebGQf(B. (3abO GSJYQV ehVhY JMQjc GdOYhi GdJCOjHjI JfGhdJ JMOjO eaghe GdehXa GdYGe(B: (3h JMbjb GdfjGHI GdEOGQjI eY GdehXa GdeJge(B: (3h CMhGd EMGdI GdeJge Edi GdeMceI GdJCOjHjI(B: (3h HjGf JGQjN JMQjc GdOYhi h BKGQg(B. (3HjfeG YGdL ehVhY SjQ GdOYhi CeGe GdeMceI GdJCOjHjI(B: (3h lNUUJ dHjGf SdWGJ GdeMceI ai eQMdI SjQ GdOYhi(B: (3h VeGfGJ GdeJge h bhGYO EKHGJ GdeSFhdjI GdJCOjHjI ai gPg GdeQMdI(B. (3ai Mjf YQV dehVhY GdHJ ai GdOYhi(B: (3h Pdc JfGhdJ GdVhGHW GdTcdjI ddMce GdJCOjHi(B: (3h GdbjhO GdhGQOI Ydi SdWI GdeMceI ai JhbjY GdYbhHI(B: (3h CMhGd GdMce HGfbVGA GdOYhi(B: (3h eQMdI GdWYf Ydi GdMce GdJCOjHi(B. (3Ke JfGhdJ NGJeI GdQSGdI HjGfG HCHQR fJGFLgG h eG CSaQJ Yfg ef JhUjGJs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGes
(3HHdjhLQGajG(B: (3UaMGJ (B615-636s
Keywords: (3GdOYhi GdJCOjHjIs; (3Mbhb GdYGedjfs; (3GdeMGce GdJCOjHjIs; (3GdLgGR GdEOGQis; (3GdeYGTs; (3SjGSGJ GdNUNUIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes